Rediscovery of the genus Saigonita Kiriakoff (Lepidoptera, Noctuidae, Agaristinae), with an updated checklist of Agaristinae from China - Huang, Si-Yao; Hou, Yong-Xiang; Chen, Liu-Sheng (Zootaxa, 2024)
The enigmatic agaristine genus Saigonita Kiriakoff, 1971 is rediscovered and recorded from Hainan, Southern China for the first time. The adults are illustrated for the first time. The generic characters of Saigonita are also discussed and modified. An updated checklist of the members of Agaristinae from China is presented, and a new synonym is proposed: Cruriopsis funebris (Moore, 1872) = Callimorpha nigralba Fang, 2000, syn. nov.